Correlation of Tympanomastoidectomy Pathological Findings With Hearing Loss In Chronic Suppurative Otitis Media Patients - Nurhalimah Nasution; Devira Zahara; Yuliani M. Lubis; Pahala Hanafi Harahap; H.R. Yusa Herwanto; Taufik Ashar (Oto Rhino Laryngologica Indonesiana, 2023)
Background: Patients with chronic suppurative otitis media (CSOM) often experience hearing loss from mild to very severe degrees. In addition, patients with CSOM often have intraoperative pathological findings. Aims of this study is to determine the correlation between intraoperative tympanomastoidectomy pathological findings with the type and degree of hearing loss using pure tone audiogram images in CSOM patients. Methods: This study is an analytic type study that uses a cross-sectional design. This research was conducted in three hospitals during October 2021 to December 2021. The sample size in this study was 37 patients who would undergo tympanomastodectomy surgery. Results: The most common pathological finding was granulation in 36 patients (97.3%) and followed by sclerotic in 31 patients (83.8%). The average patient had more than 2 pathological findings. Most of patients (78.4%) had conductive hearing loss and most of patients had moderate degree of hearing loss in 25 patients (67.6%). Based on type of hearing loss, there were significant associations with several pathological findings, namely cholesteatoma (p=0.003), defect ossicles (p=0.009), ossicular defects (p=0.001), facial nerve defects (p=0.009). In terms of the number of pathological findings, there was a significant correlation with hearing loss (p=0.004, r=0.467) and the degree of hearing loss (p=0.029, r=0.360). Conclusion: Among the pathological findings by type of hearing loss, a significant correlation was found.